Positive selection results in frequent reversible amino acid replacements in the G protein gene of human respiratory syncytial virus. - Viviane F Botosso; Paolo M de A Zanotto; Mirthes Ueda; Eurico Arruda; Alfredo E Gilio; Sandra E Vieira; Klaus E Stewien; Teresa C T Peret; Leda F Jamal; Maria I de M C Pardini; João R R Pinho; Eduardo Massad; et al. (PLoS Pathogens, 2009)
Human respiratory syncytial virus (HRSV) is the major cause of lower respiratory tract infections in children under 5 years of age and the elderly, causing annual disease outbreaks during the fall and winter. Multiple lineages of the HRSVA and HRSVB serotypes co-circulate within a single outbreak and display a strongly temporal pattern of genetic variation, with a replacement of dominant genotypes occurring during consecutive years. In the present study we utilized phylogenetic methods to detect and map sites subject to adaptive evolution in the G protein of HRSVA and HRSVB. A total of 29 and 23 amino acid sites were found to be putatively positively selected in HRSVA and HRSVB, respectively. Several of these sites defined genotypes and lineages within genotypes in both groups, and correlated well with epitopes previously described in group A. Remarkably, 18 of these positively selected tended to revert in time to a previous codon state, producing a "flip-flop" phylogenetic pattern. Such frequent evolutionary reversals in HRSV are indicative of a combination of frequent positive selection, reflecting the changing immune status of the human population, and a limited repertoire of functionally viable amino acids at specific amino acid sites.